Drugs to declare. Two pharmaceutical works attibutes to Galen - Fischer, Klaus-Dietrich (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2018)
The article examines the transmission and contents of two pseudogalenic works on drugs, the three-hundred descriptions of simples in the Ad Paternianum or The Alphabet of Galen (preserved only in Latin), and On substitute drugs (in the late-antique Latin translation).